Correlation between hemoglobin levels of mothers and children aged less than two years attending the immunization clinics in Puducherry: a cross-sectional analytical study - V. P., Khadeeja Nasreen; Ramakrishnan, Jayalakshmy; C. G., Delhi Kumar; Loganathan, Vignesh (International Journal Of Community Medicine And Public Health, 2023)
Background: Insufficient attention has been paid to the impact of maternal anemia on the hemoglobin status of children. This study aimed to estimate the correlation between the hemoglobin levels of mother’s antenatal and their current hemoglobin levels with the hemoglobin levels of their children and to find the co-occurrence of anemia among the family members of the children. Methods: A total of 200 children aged nine months to two years with their mothers were enrolled in the immunization clinics in a tertiary care hospital, and from health centres attached to it. For assessing the triple burden of anemia within the family members of the children, 50 mother-child-sibling triads were approached. The hemoglobin values of the mothers during their third trimester in the antenatal period was noted from the antenatal records. Results: 62% of the children aged less than two years were anemic and the mean hemoglobin level of the children was 10.33±1.33 gm/dl. The correlation between hemoglobin levels of children and mothers during their antenatal period was 0.15 (p: 0.03, 95% CI: 0.007 to 0.279) and 0.10 (p: 0.15, 95% CI: -0.038 to 0.236) was the correlation between current hemoglobin levels of children and mothers. 7 (14%) mother-child-sibling triads had co-occurrence of anemia in the sub-sample of 50. Conclusions: The multiple linear regression analysis confirmed that there is a weak correlation between the hemoglobin levels of mothers and children. We concluded that treating an anemic individual in a family can somehow prevent anemia in other family members.